ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DALAM MENYELESAIKAN SOAL OPEN-ENDED PADA MATERI SISTEM KOORDINAT KARTESIUS - Erlina Rindi Wulandari; Rini Setyaningsih (IKIP Siliwangi, 2023)
The purpose of this study was to describe creative thinking skills of students on the indicators of fluency, flexibility, and originality in solving open-ended questions on cartesius coordinate system materia in terms of initial ability. This study used a qualitative descriptive method with a population of the eighth grade students of SMPN 1 Plupuh, Plupuh District, Sragen Regency. Purposive sampling technique as a sampling technique so that the sample is in accordance with the specified criteria, the sample consists of 3 subjects selected from 28 students of class VIII F. The data collection technique was a written test with 3 questions, interviews with 6 questions, and documentation using a handphone camera. The research results show that the fluency indicator achieved by students with high and moderate initial abilities. Students with low initial abilities didn’t meet the fluency indicator. The flexibility indicator was only achieved by students with high initial abilities. The flexibility indicator couldn’t be achieved by students with moderate and low initial abilities. The originality indicator can be achieved by students with high and moderate initial abilities. Students with low initial abilities did’nt show self-composed solutions, so students didn’t meet the originality indicator.